PERSPECTIVE STUDY ON BRANDED PRODUCTS AND THEIR CULTURE - Suma, Ms. V. Pragnya; Krishnamohan, Dr. V. (IJRDO - Journal of Business Management, 2017)
People consume to reflect their sense of self identity. It reminds us of the socially assigned meaning to goods, often tied to desirable attributes for certain identifiable groups in specific contexts. It refers to the meanings conveyed by goods or other consumables, such as apparel, food, living, entertainment, leisure activities, cultural practices, and group membership in a broader social group. People purchase, use, and display. Consumption has been addressed primarily not only in consumer studies, but also in anthropology, sociology, economics, marketing, human ecology, and social psychology. It is very important for every brand to understand the culture of the customers in which ever place the brand sells. For example, A popular saree brand cannot aim to set up its market in Europe or USA with the aim of capturing the untamed market. This is because it is not their culture to wear a saree. While this is a very broad example, there are very intricate issues that affect the customer and make them decide whether or not to purchase the product. This research focuses on the influence of culture on consumers‟.